The Influence of Authenticity and Informative Content on Behavioural Intention Mediated by Attitude Towards Influencer in the Context of Law - Sean Eugenius; Naomi , Celine; Rifqi , Muhammad; Heriyati , Pantri (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study examines the influence of Authenticity and Informative Content from influencers on the attitudes and behavioral intentions of their followers, focusing on the phenomenon of Influencer Fatigue in Indonesia. Influencer Fatigue reflects the increasing consumer saturation and skepticism towards influencer recommendations, which is a challenge for brands that rely on influencer marketing. Through a Partial Least Square (PLS) analysis of 212 respondents, the results of the study show that Authenticity and Informative Content have a significant influence on attitudes towards influencers, which ultimately impacts followers' behavioral intentions. Authenticity has a stronger direct influence, because it creates trust and credibility instantly, while Informative Content is more effective through mediating attitudes towards influencers. These findings provide insights for marketing practitioners to choose influencers who are not only authentic, but also able to present informative content to increase follower engagement. The managerial implication is that it is important for influencers to maintain the authenticity and relevance of content to increase the effectiveness of marketing campaigns. This study also proposes further research with a qualitative and longitudinal approach to dig deeper into other factors that influence the relationship between influencers and their followers. Keywords: Influencer Fatigue, Authenticity, Informative Content, Attitude Towards Influencers, Behavioral Intention